(untitled) (Journal on studies and research of academic knowledge, 2024)
Corn is a traditional crop in Paraguay, and nitrogen (N) fertilization is one of the management practices that limits yield the most. With the objective of evaluating the effect of different levels of nitrogen fertilizer (urea) on corn production on coverage of winter green manure mixtures, an experiment was installed in the district of Encarnación with geographical coordinates south latitude -27°19’50.02" and west longitude -55°52’0.01", the experimental design was factorial, factor A was considered: two tillage systems (mixture of winter cover crops and conventional soil management method) and factor B: three doses of urea (0, 150 and 300 kg ha-1). The total number of grains per ear, weight of a thousand grains and yield were evaluated. The total number of grains per ear with a maximum value of 380 grains per ear presented a highly significant difference for the management effect, where the value was 214 grains/ear. In contrast, the difference was non-significant in terms of the effects of urea dose and the interaction. The weight of a thousand grains and yield presented highly significant differences for the individual effects and the interaction. The highest grain yield was 3.903 kg ha-1 with 300 kg ha-1 of urea on soil covered with winter green manures. The grain yield of corn is related to the number of grains per ear and the weight of grains; in turn, the soil management system influences the efficiency of urea use as fertilizer in corn, considering that it is part of the productive chain for both small, medium and large producers.